Stem‐Like Cells with Luminal Progenitor Phenotype Survive Castration in Human Prostate Cancer123. (15th May 2012) - Germann, Markus; Wetterwald, Antoinette; Guzmán‐Ramirez, Natalia; van der Pluijm, Gabri; Culig, Zoran; Cecchini, Marco G.; Williams, Elizabeth D.; Thalmann, George N.
Abstract: Castration is the standard therapy for advanced prostate cancer (PC). Although this treatment is initially effective, tumors invariably relapse as incurable, castration‐resistant PC (CRPC). Adaptation of androgen‐dependent PC cells to an androgen‐depleted environment or selection of pre‐existing, CRPC cells have been proposed as mechanisms of CRPC development. Stem cell (SC)‐like PC cells have been implicated not only as tumor initiating/maintaining in PC but also as tumor‐reinitiating cells in CRPC. Recently, castration‐resistant cells expressing the NK3 homeobox 1 (Nkx3‐1) (CARNs), the other luminal markers cytokeratin 18 (CK18) and androgen receptor (AR), and possessing SC properties, have been found in castrated mouse prostate and proposed as the cell‐of‐origin of CRPC. However, the human counterpart of CARNs has not been identified yet. Here, we demonstrate that in the human PC xenograft BM18, pre‐existing SC‐like and neuroendocrine (NE) PC cells are selected by castration and survive as totally quiescent. SC‐like BM18 cells, displaying the SC markers aldehyde dehydrogenase 1A1 or NANOG, coexpress the luminal markers NKX3‐1, CK18, and a low level of AR (AR low ) but not basal or NE markers. These CR luminal SC‐like cells, but not NE cells, reinitiate BM18 tumor growth after androgen replacement. The AR low seems to mediate directly both castration survival and tumor reinitiation. This study identifies for the first time in human PC SC‐/CARN‐like cells that may represent the cell‐of‐origin of tumor reinitiation as CRPC. This finding will be fundamental for refining the hierarchy among human PC cancer cells and may have important clinical implications. STEM CELLS 2012;30:1076–1086